Benzodithiophene bearing conjugated polymer-based surface anchoring for sensitive electrochemical glucose detection - Umut Bulut; Vuslat Oyku Sayin; Sevki Can Cevher; Ali Cirpan; Saniye Soylemez (eXPRESS Polymer Letters, 2022)
An amino-functionalized, conjugated polymer (P(BDBT)) modified glassy carbon electrode (GCE) was employed as an immobilization platform for glucose oxidase (GOx) enzyme to assemble a novel glucose biosensor. Amino groups available on the polymer backbone served as bioconjugation sites for GOx via glutaraldehyde (GA). The biosensor response to the reduction in oxygen amount because of the enzyme reaction was monitored at –0.7 V potential versus Ag/AgCl. The biosensor displayed a broad linear range between 0.1–1.0 mM glucose with a detection limit of 0.17 mM. The values of the apparent Michaelis-Menten constant (KMapp) and sensitivity were determined as 1.74 mM, and 28.17 μA/(mM·cm2), respectively. GOx immobilized P(BDBT) film displayed high stability, selectivity, and reproducibility. Cyclic voltammetry (CV) and Scanning electron microscopy (SEM) techniques were utilized for the characterization of surface modifications. The fabricated biosensor was adept at determining the amount of glucose in a commercial beverage. The simple electrochemical method for the construction of P(BDBT)/GOx biosensors could pave the way to new perspectives in developing profitable biosensors.